A Game-Based Vocabulary App for EFL Learners: Design and Development Study - Tri Wahyuni Floriasti; Nindya Hikmah Meliarany (ELLITE: Journal of English Language, Literature, and Teaching, 2026)
A game-based vocabulary application for junior high school students studying English as a foreign language (EFL) was the goal of this project. Seven stages were used in the study, which used a Research and creation (R&D) technique modified from the Jolly and Bolitho model: needs analysis, design of the syllabus and course grid, product creation, expert validation, revision, and implementation. Questionnaires, expert reviews, and classroom observations were used to gather data. The Android app featured interactive games, quizzes, audio-visual resources, and vocabulary lists. It was created with Smart Apps Creator and Canva. The app received a "very good" rating from experts for media design and content accuracy. Student responses indicated increased motivation, improved vocabulary retention, and a preference for independent learning. These findings suggest that the developed vocabulary app is an effective supplementary tool to support vocabulary acquisition in EFL contexts.